Using 360-degree panoramic technology to explore the mechanisms underlying the influence of landscape features on visual landscape quality in traditional villages - Huaheng Shen; Nor Fadzila Aziz; Xinyi Lv (Ecological Informatics)
Traditional villages, as integral components of cultures worldwide, preserve rich and irreplaceable tangible and intangible cultural heritage. However, due to China's rapid urbanization and the burgeoning rural tourism industry, the original landscape of traditional villages is being damaged. Therefore, their visual landscape quality must be scientifically evaluated and protected. This study explores the impact of landscape features on visual landscape quality. It considers Zhaoxing Dong and Basha Miao villages as case studies, utilizing 360-degree panoramic technology, a combination of scenic beauty estimation and semantic differential methods, and expert focus group discussions. The analyses revealed that eight landscape feature indicators significantly affect the visual landscape quality of traditional villages. Among these, landform diversity, waterscape, architectural style uniformity, historical sense of paved roads, folk activity landscape, and environmental cleanliness have a significant positive impact on visual landscape quality, whereas plant diversity and color richness exhibit complex bidirectional effects in enhancing visual landscape quality. Experts discussed the mechanisms underlying these influencing factors and proposed seven specific strategies and recommendations for protecting and enhancing the visual landscape quality of traditional villages: enhancing ecological aspects, preserving cultural heritage, improving infrastructure and environmental protection, encouraging community participation, developing relevant policies and regulations, promoting sustainable tourism development, and encouraging cross-sector cooperation with funding and technical support to ensure sustainable development.